SURFACE-ENHANCED RAMAN SPECTROSCOPY (SERS) USING SILVER NANOSTARS FOR THE MULTIPLEXED DETECTION OF DISEASE BIOMARKERS IN SERUM - Nadine Tchuente; Michel Ngassa; Elvis Ewane (Yayasan Adra Karima Hubbi, 2025)
Early and accurate detection of disease biomarkers in serum is essential for clinical diagnosis, prognosis, and precision medicine, yet conventional immunoassays often rely on labeled reagents, multiple processing steps, and limited multiplexing capability. Surface-Enhanced Raman Spectroscopy (SERS) offers label-free molecular specificity, but its clinical application has been constrained by reproducibility and sensitivity challenges in complex biological matrices. This study aims to develop a silver nanostar–based SERS platform for the multiplexed detection of disease biomarkers directly in serum. An experimental nanobiosensing approach was employed, involving the synthesis of shape-controlled silver nanostars, surface functionalization with biomolecular recognition elements, physicochemical characterization, and SERS-based analytical evaluation in serum samples. The results demonstrate that silver nanostars generate strong and stable Raman enhancement, enabling clear discrimination of multiple biomarker signatures at low nanomolar concentrations. High linearity, acceptable reproducibility, and minimal matrix interference were achieved under multiplexed conditions. Comparative analysis confirmed superior performance of nanostars relative to conventional spherical nanoparticles. In conclusion, silver nanostar–based SERS provides a robust, label-free, and highly sensitive platform for multiplexed serum biomarker detection. This approach holds significant potential for advancing clinical diagnostics and translational bioanalytical applications.